Konsep Butterfly Effect dalam Psikologi Positif - Faliha Muthmainah (Flourishing Journal, 2022)
The butterfly effect is a term used in various studies, including psychology. Not too down to earth; however, some figures use this term. In this case, the writing of this article is to dig deeper into the concept of the butterfly effect from a positive psychology perspective. The idea of the Butterfly effect in positive psychology refers to the fact that small actions taken by one person can significantly impact themselves and other people or the environment around them. The method used is a literature review. The results obtained from the literature search show the term butterfly effect in positive psychology often uses the term effervescent or ripple effect. By paying attention to small practices such as promoting kindness, sincerity, and optimism, these small actions can contribute to happiness, well-being, and attachment to those around us. Ultimately, the Butterfly effect in positive psychology can positively impact mental and physical health and the overall social well-being of individuals, communities and even the nation. Abstrak Butterfly effect merupakan istilah yang digunakan dalam berbagai studi termasuk psikologi. tidak terlalu membumi namun, beberapa tokoh menggunakan istilah ini. Dalam hal ini tulisan dari artikel ini untuk menggali lebih dalam konsep butterfly effect dalam perspektif psikologi positif. Konsep Butterfly effect dalam psikologi positif mengacu pada fakta bahwa tindakan kecil yang dilakukan oleh satu orang dapat memberikan dampak yang besar pada dirinya dan orang lain atau lingkungan sekitarnya. Metode yang digunakan adalah literature review. Hasil yang didapatkan dari penelusuran pustaka, istilah butterfly effect dalam psikologi positif sering mengunakan penggunaan istilah effervensce atau ripple effect. Dengan memberikan perhatian terhadap praktik-praktik kecil seperti mempromosikan kebaikan, ketulusan, dan optimisme, maka perbuatan kecil ini dapat berkontribusi pada kebahagiaan, kesejahteraan, serta keterikatan pada orang di sekitar kita. Pada akhirnya, Butterfly effect dalam psikologi positif dapat berdampak positif pada kesehatan mental dan fisik serta kesejahteraan dan sosial secara menyeluruh pada individu, komunitas bahkan bangsa sebagai suatu kesatuan.